Swell observations on Soviet research ships during Monsoon Experiment (MONEX) 1977 - Part I : The equatorial region - MUKHERJEE, A. K.; SIVARAMAKRISHNAN, T. R.; SATYANARAYANA, P. (MAUSAM, 1980)
Observations of swell waves taken on board Soviet Research Ships, which worked during Monsoon Experiment of 1977 have been analysed. The first period is the end of May and the begining of June when the Ships moved in formation along Equator. Swells over equator during the onset of monsoon has been studied from these data. The second period when the ships again went to Equator and remained stationary were towards the end of July. Swells, during this period therefore represent those over equator when monsoon is in full swing. It is found that equator, is an area of low swells. Heights are less during monsoon than at the onset period.